Diseño de la automatización de la cámara climatizada para pruebas de equipos y materiales (2019)
In this research project, the design of the automation of the climate chamber for testing equipment and materials was carried out, with the aim of controlling and regulating atmospheric conditions inside by means of an automatic system; This system is made up of measuring instruments, controllers, control and supervision systems. On the other hand, the project includes the evaluation of the instrumentation and control requirements present in the climate chamber, required by the Technical Regulations (RETIQ) and NTC 5891 and NTC 5310 that govern the testing of artefacts of refrigeration domestic and commercial. In addition, in this elaboration, instruments and control were selected through the results acquired in a mathematical model proposed in the development of the project. In the same way, the control and supervision systems were established in a virtual instrumentation software, in order to recreate in an interface. Finally, in the research project, the parameters associated with air conditioning, programming and costs related to automation are determined.